Diagnostic Value of C-reactive Protein and Interleukin-8 in Risk Stratification of Febrile Neutropenic Children with Allogeneic Hematopoietic Stem Cell Transplantation - Jaing, Tang-Her (Sci Rep, 2020)
In this analysis, the levels of CRP and IL-8 were employed as a guide for designing the duration of antibiotics administration in the condition of febrile neutropenia. The importance of laboratory biomarkers is in the early diagnosis of critical illness and adjustment of further management. IL-8 is a useful biomarker for the early identification of critically ill patients, compared to CRP in FN.